2021
DOI: 10.3390/ani11020322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Anthocyanin-Extracted Residue on Meat Oxidation and Fatty Acid Profile of Male Dairy Cattle

Abstract: This research aimed to evaluate the effects of anthocyanin-extracted residue (AER) in the diet of cattle on meat oxidation during storage and on the fatty acid profiles of the meat. Sixteen male dairy cattle (average body weight 160 ± 10.6 kg) were allotted to feed in a completely randomized design (CRD) with four levels of AER supplementation, 0, 20, 40, and 60 g/kg dry matter (DM) in the total mixed ration (TMR). These TMR diets were fed ad libitum to the cattle throughout the trial. At the end of the feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 71 publications
8
22
1
Order By: Relevance
“…Indeed, lipid oxidation has a negative effect on meat, whereas it can help to form pleasant aromas in some cases [ 42 ]. Consistent with our results, Prommachart et al [ 43 ] who showed that purple corn anthocyanin extracted residue in cattle diet could decrease lipid oxidation and increase UFA, might improve flavor compounds in meat.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, lipid oxidation has a negative effect on meat, whereas it can help to form pleasant aromas in some cases [ 42 ]. Consistent with our results, Prommachart et al [ 43 ] who showed that purple corn anthocyanin extracted residue in cattle diet could decrease lipid oxidation and increase UFA, might improve flavor compounds in meat.…”
Section: Discussionsupporting
confidence: 93%
“…The antioxidant activities of anthocyanin also affect increased desaturase enzymes activity for converting monounsaturated fatty acid (MUFA) to PUFA or inserting additional unsaturated bonds into already existing PUFA [17,27]. Studies have suggested that PUFAs have antimicrobial activities and are toxic to cellulolytic microorganisms by altering the bacterial cell membranes and the various essential processes that occur within and at the membrane; therefore, PUFAs can also reduce the microbial colonization with the fed particles and reduce the rumen digestibility of fiber [80].…”
Section: Effects On Ruminal Digestibility Volatile Fatty Acids and Methane Emissionmentioning
confidence: 99%
“…In beef, by-products rich in polyphenols can alter the composition of fatty acids in meat through the effects of antioxidants on ruminal bacteria and the mechanism of absorption and transportation of these fatty acids from small intestine to muscle. However, some levels of antioxidants, primarily polyphenols and anthocyanins in ruminant diets, are associated with increases in the proportions of n-3 and n-6 PUFA [27]. Indeed, improving the contents of n-3 and n-6 PUFA in ruminant products have positive effects on human health, i.e., rumenic acid and LA isomers (cis-9, trans-11), which have demonstrated effects such as antiatherosclerosis, anticarcinogenic, antidiabetic, and anti-inflammatory activities in laboratory animals, and anticholesterolemic and anti-atherosclerosis effects in humans.…”
Section: Anthocyanins and Polyphenols In Milk And Meat Fatty Acids Compositionmentioning
confidence: 99%
See 2 more Smart Citations